The diagnostic value of 68Ga-NOTA-MAL-Cys-MZHER2:342 PET/CT imaging for HER2-positive lung adenocarcinoma - Li, Shu; Wang, Ke; Zhu, Xue; Pan, Donghui; Wang, Ling; Guo, Xu; Gao, Xiaomin; Luo, Qing; Wang, Xun (Frontiers in Medicine, 2024)
The human epidermal growth factor receptor 2 gene (HER2) has been identified as a potential therapeutic target in lung adenocarcinoma (LUAD). Non-invasive Positron Emission Tomography (PET) imaging provides a reliable strategy for in vivo determination of HER2 expression through whole-body detection of abnormalities. The PET tracer 68 Ga-NOTA-MAL-Cys-MZHER2:342 has shown promising results for HER2-positive breast and gastric cancers. This study aims to evaluate the performance of 68 Ga-NOTA-MAL-Cys-MZHER2:342 in vitro and in vivo models, as well as in clinical patients with HER2-positive LUAD.Methods: NOTA-MAL-Cys-MZHER2:342 was synthesized and labeled with 68 Ga. Cell uptake, cell binding ability, and stability studies of 68 Ga-NOTA-MAL-Cys-MZHER2:342 were assessed both in Calu-3 Lung cancer (LC) cell line and in normal mice. In vivo assessment in tumor-bearing mice was conducted using microPET imaging and biodistribution experiments. Additionally, preliminary PET/CT imaging analysis was performed on HER2-positive lung cancer patients.Results: 68 Ga-NOTA-MAL-Cys-MZHER2:342 was prepared with a radiochemical purity exceeding 95%. The tracer demonstrated high cell uptake in HER2-overexpressing Calu-3 cells, with an IC50 of 158.9 adequate 1.73 nM. Good stability was exhibited both in vitro and in vivo. MicroPET imaging of Calu-3-bearing mice revealed high tumor uptake and notable tumor-to-background ratios. Positive outcomes were also observed in two HER2-positive LUAD patients.